Cerebrospinal fluid findings in adult patients with obsessive-compulsive disorder: A retrospective analysis of 54 samples. (21st April 2023) - Pankratz, Benjamin; von Zedtwitz, Katharina; Runge, Kimon; Denzel, Dominik; Nickel, Kathrin; Schlump, Andrea; Pitsch, Karoline; Maier, Simon; Dersch, Rick; Voderholzer, Ulrich; Domschke, Katharina; Tebartz van Elst, Ludger; et al.
Abstract: Objectives: Obsessive-compulsive disorder (OCD) can rarely be associated with immunological aetiologies, most notably in Paediatric Autoimmune Neuropsychiatric Disorder Associated with Streptococcal Infections and possibly in autoimmune encephalitis. As cerebrospinal fluid (CSF) analysis is a sensitive method for assessing neuroinflammation, this retrospective study analysed basic CSF parameters and well-characterised as well as novel neuronal autoantibodies in OCD to screen for signs of autoimmunity. Methods: Basic CSF findings of 54 adult OCD patients suspected of an organic aetiology were retrospectively compared to a control group of mentally healthy patients ( N = 39) with idiopathic intracranial hypertension. Further subgroup analysis included testing for well-characterised neuronal IgG autoantibodies and tissue-based assays using indirect immunofluorescence to screen for novel brain autoantibodies. Results: Elevated protein in the CSF of OCD patients compared to the control group ( p = 0.043) was identified. Inflammatory markers (pleocytosis/oligoclonal bands/increased IgG-index) were detected in 7% of all patients with OCD. Well-characterised neuronal autoantibodies were not found in any OCD patient, whereas 6/18 (33%) CSF samples showed binding on mouse brain sections in tissue-based assays (binding to neuropil in the basal ganglia/brainstem, cilia of granule cells, blood vessels, nuclear/perinuclear structures). Conclusions: While elevated CSF protein is merely a weak indicator of blood CSF barrier dysfunction, the presence of inflammatory CSF changes and novel brain autoantibodies in CSF may indicate OCD subtypes with inflammatory pathomechanism and supports the hypothesis of a rare "autoimmune OCD" subtype.